Comparative study of synchronization methods of fractional order chaotic systems - Singh Ajit K.; Yadav Vijay K.; Das S. (Nonlinear Engineering, 2016)
In this article, the active control method and the backstepping method are used during the synchronization of fractional order chaotic systems. The salient feature of the article is the analysis of time of synchronization between fractional order Chen and Qi systems using both the methods. Numerical simulation and graphical results clearly exhibit that backstepping approach is better than active control method for synchronization of the considered pair of systems, as it takes less time to synchronize while using the first one compare to second one.